Tunable photonic devices by 3D laser printing of liquid crystal elastomers - Woska, Simon; Münchinger, Alexander; Beutel, Dominik; Blasco, Eva; Hessenauer, Jannis; Karayel, Osman; Rietz, Pascal; Pfleging, Stefan; Oberle, Roman; Rockstuhl, Carsten; Wegener, Martin; Kalt, Heinz (Optical materials express, 2020)
Liquid crystal elastomers (LCEs) are highly suitable materials for the fabrication of flexible photonic elements due to their ability for directional actuation induced by external stimuli. 3D laser printing (3DLP) is a well-established method to realize complex photonic architectures. In this paper, we present the technological adaptations necessary to combine the actuation-controlled flexibility of LCE with the design options inherent to 3DLP to realize a platform for tunable photonics. The role of birefringence of the LCE in the 3DLP fabrication is addressed and theoretically modelled. We demonstrate how LCEs can be used both as a flexible substrate for arrays of rigid photonic elements and as a material for tunable photonic structures itself. Flexible coupling of two optical whispering gallery mode cavities and full spectral tunability of a single cavity are presented as exemplary applications.
First published: 07 October 2020
Gesehen am 12.10.2022